2016
DOI: 10.3402/gha.v9.32178
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing health facilities for childbirth: a multilevel study in three districts of Gujarat, India

Abstract: Background: Bypassing available facilities for childbirth has important implications for maternal health service delivery and human resources within a health system. The results are the additional expenses imposed on the woman and her family, as well as the inefficient use of health system resources. Bypassing often indicates a lack of confidence in the care provided by the facility nearest to the mother, which implies a level of dysfunctionality that the health system needs to address. Over the past decade, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 17 publications
7
49
5
Order By: Relevance
“…However, on the other side, "bypassing" of health facilities i.e. delivery in a facility that is not the closest one to a mother's home has been described in several studies [12][13][14][15][16][17]. While giving birth in a higherlevel facility might provide women with better care and might be safer for the mother and her newborn, overmedicalisation in such facilities has been described and costs maybe higher for both i) the health care system as well as for i) women and their families [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, on the other side, "bypassing" of health facilities i.e. delivery in a facility that is not the closest one to a mother's home has been described in several studies [12][13][14][15][16][17]. While giving birth in a higherlevel facility might provide women with better care and might be safer for the mother and her newborn, overmedicalisation in such facilities has been described and costs maybe higher for both i) the health care system as well as for i) women and their families [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Background factors affecting the overcrowding include self-referral and free choice in deciding the place of delivery. Studies have suggested that self-referral is a product of a lack of confidence in the quality of care or unavailability of services in first-line facilities [12,[16][17][18][19]. However, this may not be the case in our study site, because health centres are the most used facility for childbirth.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to recent studies in Mozambique and Tanzania, Ghana and India also in Florida and Switzerland bypassing was described. The reasons why patients seeking care at higher level facilities were in all studies better quality of service, better access to advanced technology and competence of the staff, despite the distance they have to travel [9,15,[28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 94%